Thalidomide-induced teratogenesis: History and mechanisms - Vargesson, Neil (Birth defects research. Part C. Embryo today, 2015)
Nearly 60 years ago thalidomide was prescribed to treat morning sickness in pregnant women. What followed was the biggest man‐made medical disaster ever, where over 10,000 children were born with a range of severe and debilitating malformations. Despite this, the drug is now used successfully to treat a range of adult conditions, including multiple myeloma and complications of leprosy. Tragically, a new generation of thalidomide damaged children has been identified in Brazil. Yet, how thalidomide caused its devastating effects in the forming embryo remains unclear. However, studies in the past few years have greatly enhanced our understanding of the molecular mechanisms the drug. This review will look at the history of the drug, and the range and type of damage the drug caused, and outline the mechanisms of action the drug uses including recent molecular advances and new findings. Some of the remaining challenges facing thalidomide biologists are also discussed. Birth Defects Research (Part C) 105:140–156, 2015. © 2015 The Authors Birth Defects Research Part C: Embryo Today: Reviews Published by Wiley Periodicals, Inc.